Implementasi Isi Doa Rasul Paulus Berdasarkan Surat Efesus 3:14-21 Bagi Peserta Didik Kelas Vi Di Sd Budya Wacana I Yogyakarta Tahun Ajaran 2020/2021 - Astuti, Dewi; Agustin, Eudia Angelia Ika; Uriptiningsih, Ana Lestari (Basileus Eirene: Jurnal Agama dan Pendidikan, 2022)
The purpose of this study is first, to determine the level of implementation of the contents of the Apostle Paul's Prayer based on Ephesians 3:14-21 for class VI students at SD Budya Wacana I Yogyakarta. Second, the most dominant dimension determines the implementation of the contents of the Apostle Paul's Prayer based on Ephesians 3:14-21 for Students at SD Budya Wacana I Yogyakarta. The research uses quantitative methods, namely collecting information and data by means of site surveys, interviews and submitting the data obtained. The tests used are instrument validation and reliability tests and normality tests. To test the hypothesis using the Confidence Interval formula at a significance level of 5%, the regression significance test (Freg) and the one-way variance test (one way ANOVA). The results of the first study, from the calculation of the validation test the results of the respondents' answers from 36 items using the Pearson formula stated 36 item all items are valid. Second, from the reliability test using SPSS 25 software with the Alpha formula of 36 items, it was stated that 57 respondents/respondents were declared 100% valid as respondents with a reliability level of 0.949 located between 0.8 - 1 which means it is included in the very reliable criteria. Third, from the normality test for the Y variable using SPSS 25 software with the Kolmogorof-Smirnov formula, the probability is stated based on the table that for the D1 variable (Rooted in Christ) 0.142, D2 (Knowing the Love of Christ) 0.136, and Y 0.113 has a value above significant 0, 05 means that the variables D1, D2, and Y are normally distributed and hypothesis testing can be done using parametric rules.